2007
DOI: 10.1007/s00167-007-0379-8
|View full text |Cite
|
Sign up to set email alerts
|

Septic arthritis with Staphylococcus lugdunensis following arthroscopic ACL revision with BPTB allograft

Abstract: Septic arthritis following anterior cruciate ligament reconstruction is an uncommon but a serious complication resulting in six times greater hospital costs than that of uncomplicated ACL surgery and an inferior postoperative activity level. Promptly initiating a specific antibiotic therapy is the most critical treatment, followed by open or arthroscopic joint decompression, debridement and lavage. Staphylococcus lugdunensis is a coagulase-negative staphylococcus predominantly infecting the skin and soft tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
(53 reference statements)
1
24
0
2
Order By: Relevance
“…Another study revealed that during a 40-month period, S. lugdunensis accounted for 1% of the 601 CNS obtained from patients with orthopedic clinical infections, including surgical wounds and infected prostheses (3). Temporal bone osteomyelitis and three cases of S. lugdunensis infective arthritis following surgical procedures have been reported (60,118,132,181).…”
Section: Bone and Joint Infectionmentioning
confidence: 99%
“…Another study revealed that during a 40-month period, S. lugdunensis accounted for 1% of the 601 CNS obtained from patients with orthopedic clinical infections, including surgical wounds and infected prostheses (3). Temporal bone osteomyelitis and three cases of S. lugdunensis infective arthritis following surgical procedures have been reported (60,118,132,181).…”
Section: Bone and Joint Infectionmentioning
confidence: 99%
“…11 Like many polymeric or metallic implants, LARS ligaments can cause serious side effects such as severe synovitis. 12,13 Coating with organic materials of good biocompatibility on artificial graft surface has received increasing interest as an alternative option. In our previous work, hydroxyapatite (HAP) and bioglass coating on PET artificial ligaments could promote the cell compatibility of grafts.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] There is concern, however, that introducing tissue from deceased human donors may increase the risk of infection. [22][23][24][25][26][27][28][29][30][31][32][33] Studies to date comparing allograft vs autograft tissue for ACL reconstruction have not found statistically significant differences in infection risk but may have been underpowered. [3][4][5]16 Given these concerns, we conducted a study to assess risk factors for infection following ACL reconstruction, with particular attention to the role played by the type of graft implanted.…”
mentioning
confidence: 99%